2020
DOI: 10.2147/cmar.s263767
|View full text |Cite
|
Sign up to set email alerts
|

<p>Insulin Reduces the Efficacy of Vemurafenib and Trametinib in Melanoma Cells</p>

Abstract: Background: Despite the progress made in the clinical management of metastatic melanoma, a patient's response to treatment cannot be fully predicted, and intrinsic or acquired resistance that is developed in most melanoma patients warrants further research efforts. In addition to genetic factors, microenvironmental input should be considered to explain the diversity of response to treatment among melanoma patients. In this study, we evaluated the impact of insulin on patient-derived BRAF V600E melanoma cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 110 publications
(140 reference statements)
0
6
0
Order By: Relevance
“…Clinical reports indicate that MGMT promoter is methylated, and thus suppressed, in about 21.5–35% of metastatic melanomas [ 119 , 121 , 122 , 123 ], which entails that inhibition of BRAF, MEK and HDAC could potentially benefit a large number of melanoma patients. Compatible with findings by Maertens and colleagues, our group has recently reported that vemurafenib and trametinib reduced the expression of BRIP1, BRCA1 and BRCA2 in 4 out of 5 patient-derived BRAF V600E cell lines [ 42 ]. In addition, we found that insulin modulated the response of melanoma cells to MAPK inhibition by attenuating drug-induced reduction in the expression of DNA repair genes, deregulation of glutathione homeostasis and increase in DNA damage, which altogether led to substantially reduced cytotoxicity of vemurafenib and trametinib [ 42 ].…”
Section: Mitogen-activated Protein Kinase Inhibitorsmentioning
confidence: 51%
See 2 more Smart Citations
“…Clinical reports indicate that MGMT promoter is methylated, and thus suppressed, in about 21.5–35% of metastatic melanomas [ 119 , 121 , 122 , 123 ], which entails that inhibition of BRAF, MEK and HDAC could potentially benefit a large number of melanoma patients. Compatible with findings by Maertens and colleagues, our group has recently reported that vemurafenib and trametinib reduced the expression of BRIP1, BRCA1 and BRCA2 in 4 out of 5 patient-derived BRAF V600E cell lines [ 42 ]. In addition, we found that insulin modulated the response of melanoma cells to MAPK inhibition by attenuating drug-induced reduction in the expression of DNA repair genes, deregulation of glutathione homeostasis and increase in DNA damage, which altogether led to substantially reduced cytotoxicity of vemurafenib and trametinib [ 42 ].…”
Section: Mitogen-activated Protein Kinase Inhibitorsmentioning
confidence: 51%
“…Compatible with findings by Maertens and colleagues, our group has recently reported that vemurafenib and trametinib reduced the expression of BRIP1, BRCA1 and BRCA2 in 4 out of 5 patient-derived BRAF V600E cell lines [ 42 ]. In addition, we found that insulin modulated the response of melanoma cells to MAPK inhibition by attenuating drug-induced reduction in the expression of DNA repair genes, deregulation of glutathione homeostasis and increase in DNA damage, which altogether led to substantially reduced cytotoxicity of vemurafenib and trametinib [ 42 ]. The role of MAPK-targeted therapeutics in deregulation of DNA repair was also confirmed in other cancer types: BRAF V600E inhibition using vemurafenib was shown to suppress double strand break repair and sensitize thyroid cancer cells to ionizing radiation [ 124 ], and MEK inhibition using trametinib induced similar effects in pancreatic cancer cells [ 125 ].…”
Section: Mitogen-activated Protein Kinase Inhibitorsmentioning
confidence: 51%
See 1 more Smart Citation
“…The main cause of this noted poor prognosis is attributed to BRAF inhibitor-mediated compensatory mechanisms. These compensatory mechanisms include elevation of ARAF and CRAF proteins, a mechanism through which melanoma cells sustain the activation of MAPK activity during BRAF inhibitors treatment [206][207][208]. Although BRAF inhibitor-resistant cells remain sensitive to MEK inhibitors, the resistance of these melanoma cells to various structurally different MEK inhibitors can be mediated by the generation of the compensatory mechanism via activation of RTKs such as IGF-1R [205][206][207][208].…”
Section: Mechanisms Of Melanoma Treatment Failure and Recurrencementioning
confidence: 99%
“…Like other cells with a melanocyte origin, melanoma cells express IGF-1R. Importantly, MEK inhibitor-resistant melanoma cells demonstrate higher surface levels of IGF-1R when compared to BRAF-sensitive melanoma cells [205][206][207][208]. As such, IGF-1R is known to play an important role in tumor progression and drug resistance [209].…”
Section: Mechanisms Of Melanoma Treatment Failure and Recurrencementioning
confidence: 99%